First Reported Death in India during MRgFUS: A Case Report - Bhise, S S; Chavan, G S; Nanandkar, S D; Chikhalkar, B G; Thube , H R (Journal of Indian Academy of Forensic Medicine, 2015)
Uterine adenomyosis is an important problem for women of reproductive age. Although  hysterectomy has been the traditional treatment for symptomatic fibroids, many child bearing women are  interested in a less invasive therapy. Magnetic resonance-guided focused ultrasound (MRgFUS) is a new  technique for treating a variety of solid tumors. The procedure is completely noninvasive. It is performed  as an outpatient procedure and the patient can resume her normal activities the day following the  procedure. A 39 years female came with c/o dysmenorrheal, menorrhagia and polymenorrhagia since 5  years. Patient’s vitals were normal before procedure but patient suddenly collapsed and died after  procedure. Dead body was forwarded for postmortem examination. During postmortem it was found that  there was 3 liter of blood in peritoneum. As this is the safest outpatient procedure then what was the  reason for this 3 liter of blood in abdominal cavity…?
Keywords: MRgFUS; Fibroids; Uterine Leiomyoma; MR-Guided; Magnetic Resonance Imaging; Ablation